X-ray stability and degradation mechanism of lead halide perovskites and lead halides. Issue 21 (25th May 2021) - Svanström, Sebastian; García Fernández, Alberto; Sloboda, Tamara; Jacobsson, T. Jesper; Rensmo, Håkan; Cappel, Ute B.
Abstract : The degradation of lead halides perovskites under X-ray irradiation follows different pathways and has different kinetics depending on if the radiolysis of the organic cation or the lead halide cage is dominant. Abstract : Lead halide perovskites have become a leading material in the field of emerging photovoltaics and optoelectronics. Significant progress has been achieved in improving the intrinsic properties and environmental stability of these materials. However, the stability of lead halide perovskites to ionising radiation has not been widely investigated. In this study, we investigated the radiolysis of lead halide perovskites with organic and inorganic cations under X-ray irradiation using synchrotron based hard X-ray photoelectron spectroscopy. We found that fully inorganic perovskites are significantly more stable than those containing organic cations. In general, the degradation occurs through two different, but not mutually exclusive, pathways/mechanisms. One pathway is induced by radiolysis of the lead halide cage into halide salts, halogen gas and metallic lead and appears to be catalysed by defects in the perovskite. The other pathway is induced by the radiolysis of the organic cation which leads to formation of organic degradation products and the collapse of the perovskite structure. In the case of Cs0.17 FA0.83 PbI3, these reactions result in products with a lead to halide ratio of 1 : 2 and no formation of metallic lead. The radiolysis of the organic cation was shown to be a first order reaction with regards to the FA + concentration and proportional to the X-ray flux density with a radiolysis rate constant of 1.6 × 10 −18 cm 2 per photon at 3 keV or 3.3 cm 2 mJ −1 . These results provide valuable insight for the use of lead halide perovskite based devices in high radiation environments, such as in space environments and X-ray detectors, as well as for investigations of lead halide perovskites using X-ray based techniques.